Histopathological Biomarkers of Exposure to Monocyclic Aromatic Hydrocarbons in Clarias Ggariepinus (African Catfish) - Doherty, Funmilayo V.; Adeola, Abdullahi; Aneyo, Idowu A.; Otitoloju, Adebayo A. (Journal of Science and Technology, 2019)
The pollution of the environment with petroleum products through spills in oil producing countries has resulted in the widespread distribution of benzene, toluene, ethylbenzene and xylene. The aim of this study was to identify histopathological alterations in Clarias gariepinus (catfish) that can be used as biological markers for detection of petroleum hydrocarbon contamination which can be included in monitoring programmes. The toxicological evaluations of benzene, toluene, ethylbenzene and xylene were carried out against Clarias gariepinus. The histopathological effects of benzene, toluene, ethylbenzene and xylene (BTEX) on different organs were investigated in C. gariepinus, Tilapia zillii, and Chrysichthys nigrodigitatus taken from the impacted areas of the Lagos Lagoon. Toxicological evaluations of the monocyclic aromatic components, benzene, toluene, ethylbenzene and xylene on Clarias gariepinus showed that ethylbenzene (0.479 ml/l) was the most toxic compound tested followed by xylene (0.519 ml/l), benzene (0.666 ml/l) and toluene (1.190 ml/l). The results from the histological study identified necrosis and deformation of the gills, inflammations in the liver, and wrinkling of the oocyte membrane in the gonads of fish, as good histopathological biomarkers of hydrocarbon related stressors. The combination of chemical analysis with these identified biomarkers can be used during environmental monitoring programmes for the protection of aquatic ecosystem.